2002
DOI: 10.1073/pnas.082115999
|View full text |Cite
|
Sign up to set email alerts
|

Genes on chromosomes 1 and 13 have significant effects on Ascaris infection

Abstract: Nematode parasites show a characteristic aggregated distribution among hosts. This observation has important implications for pathogenesis, immunology, and control of these infections, but the relative roles of environment and genetics in determining these patterns have remained uncertain. This paper presents the results of the first genome scan for susceptibility to infection with roundworm (Ascaris lumbricoides). Data on 375 genetic markers were generated for each of 444 members of a genetically isolated Nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
1
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 32 publications
5
109
1
8
Order By: Relevance
“…Previous studies have suggested that there is a substantial genetic component to susceptibility to Ascaris infection in humans; the quantitative trait loci on chromosomes 1 and 13 provide strong evidence for the influence of at least two discrete genes on Ascaris burden. 11 Although intestinal helminth infection is mutually correlated with other factors to some degree, this infection does contribute a portion of risk for the development of anemia conditioned on the presence of other risk factors. For this reason, when analyzed alone or when independent of other risk factors, intestinal helminths may not seem to be a major factor in nutritional deficits, as has been the conclusion of this group in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that there is a substantial genetic component to susceptibility to Ascaris infection in humans; the quantitative trait loci on chromosomes 1 and 13 provide strong evidence for the influence of at least two discrete genes on Ascaris burden. 11 Although intestinal helminth infection is mutually correlated with other factors to some degree, this infection does contribute a portion of risk for the development of anemia conditioned on the presence of other risk factors. For this reason, when analyzed alone or when independent of other risk factors, intestinal helminths may not seem to be a major factor in nutritional deficits, as has been the conclusion of this group in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Few studies have explored the joint effect of multiple simultaneous helminth infection and inadequate iron consumption on anemia. Fewer still have looked at light or moderate infections, despite these representing > 90% of all infections, 11 or the fact that a significant percentage are infected by two or more species. The need for treatment of most heavy infections is fairly clear-cut, but there is less certain support for treatment of the much more common light-or moderateintensity infections.…”
Section: Introductionmentioning
confidence: 99%
“…Like most other helminths Ascaris show an aggregated distribution in their hosts, and although recent studies have suggested a genetic basis to this phenomenon in humans (Williams-Blangero et al 2002), behavioural, immunological and physiological factors are also thought to play key roles in causing predisposition (McSharry et al 1999 ;Holland and Boes, 2002). The mechanistic basis of predisposition is not understood, but it may well be initiated during the early phase of infection.…”
Section: Introductionmentioning
confidence: 99%
“…If exact multipoint IBD sharing estimation is limited to moderate-sized pedigrees as already noted for qualitative traits, approximate methods, such as correlation-based 34 or MCMC 35 algorithms, allow to use VC for much larger pedigrees. An illustration of the use of VC in isolated populations is the work of Williams-Blangero et al, 36 who have conducted a linkage analysis on susceptibility to Ascaris infection (a roundworm) based on a 444-member pedigree from the Jirels, an isolated Nepalese population. Individuals were selected based only on pedigree informativeness and not with respect to Ascaris phenotype.…”
Section: Quantitative Traitsmentioning
confidence: 99%